PENGARUH PROFITABILITAS, LIKUIDITAS DAN LEVERAGE TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Nafa Rahmafadilah, - (2019)
This study aims to determine the effect of Profitability which is proxied Return On Equity (ROE), Liquidity which is proxied by Current Ratio (CR) and Leverage that is proxied by Debt to Equity Ratio (DER) toward Dividend Policy which is proxied by Dividend Payout Ratio (DPR). The population in this study are companies listed on the Indonesia Stock Exchange and the sample of this study are LQ45 companies listed on the Indonesian Stock Exchange for the 2014-2017. The sample selection technique used was purposive sampling and obtained 21 LQ45 companies with a study research period of four years to obtain 84 units of samples. Data analysis was done using Microsoft Excel 2010 and hypothesis testing in this research using Data Panel Regression Analysis with E-Views 9.0 program and significance level of 5%. The result of the research show that (1) there is significant positive influence profitability (ROE) on dividend policy (DPR), (2) there is no influence liquidity (CR) on dividend policy (DPR), (3) there is significant negative influence leverage (DER) on dividend policy (DPR).